A EXPLORATION OF EFL STUDENTS’ WRITING EXPERIENCES, CHALLENGES, AND STRATEGIES AT UNIVERSITAS SERANG RAYA - Muhammad Rifqi; Rizal Fauzi; Rahmatullah; Alfalah Restu Prasetyo; Amelliahtus Soliha (Cakrawala Pedagogik, 2023)
Writing is a fundamental yet demanding competency for university students in the English as a Foreign Language (EFL) context. This research aims to explore the writing experiences of EFL students at Universitas Serang Raya, specifically focusing on the challenges they encounter and the strategies they employ to overcome these difficulties. To address this objective, the study formulated a central question: How do students perceive their writing process and what strategies do they utilize in developing their academic writing skills? This study employed a qualitative approach with a case study design. Data were collected from eight English Education students through semi-structured interviews, reflective writing essays, and document analysis of student work. The participants were selected using purposive sampling based on their completion of Academic Writing courses. The findings, derived through thematic analysis, revealed three primary themes: (1) significant linguistic and affective challenges, including limited vocabulary, grammatical errors, and low self-confidence; (2) a reliance on compensatory strategies such as digital tools and translation from the native language; and (3) a preference for process-oriented and interactive learning environments. The results suggest that while students are proactive in using digital resources, their dependence on translation indicates a need for more integrated strategic training. This study provides practical implications for educators to design more responsive, process-based writing instructions that address both the cognitive and affective needs of EFL learners.